2023
DOI: 10.1021/acs.analchem.2c05127
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic Reticulum-Targeted Two-Photon Fluorescent Probe for the Detection of Nitroxyl in a Parkinson’s Disease Model

Abstract: Nitroxyl (HNO) and endoplasmic reticulum (ER) stress are considered to play important effects in the administration of many pathological processes of Parkinson’s disease (PD). However, the intricate relationship between the neurotoxicity of HNO and ER stress in the processes of PD is still unknown. To completely comprehend the pathogenic activity of HNO during ER stress and achieve early diagnosis of PD, developing sensitive tools for HNO sensing in vivo is essential. In this work, a two-photon fluorescent pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Molecules 2024, 29, x FOR PEER REVIEW 2 of 19 TPE probes have been developed for detecting β-amyloid plaques and tau aggregates [6][7][8][9][10][11][12][13]. However, to the best of our knowledge, there remains a lack of dedicated probes for α-synuclein (α-syn) aggregates.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Molecules 2024, 29, x FOR PEER REVIEW 2 of 19 TPE probes have been developed for detecting β-amyloid plaques and tau aggregates [6][7][8][9][10][11][12][13]. However, to the best of our knowledge, there remains a lack of dedicated probes for α-synuclein (α-syn) aggregates.…”
Section: Resultsmentioning
confidence: 99%
“…Optical imaging-based approaches based on two-photon excitation (TPE), on the other hand, can allow for both high spatial and temporal resolution. To date, numerous TPE probes have been developed for detecting β-amyloid plaques and tau aggregates [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. However, to the best of our knowledge, there remains a lack of dedicated probes for α-synuclein (α-syn) aggregates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…S12, ESI†). 14 The results indicated that probe NF could be used as an efficient imaging tool for HNO detection in vivo . Above all, ratiometric probe NF can selectively and rapidly detect HNO in vitro and in complex living systems.…”
mentioning
confidence: 91%
“…However, the specific physiological mechanisms of nitroxide are still not well known due to the lack of effective detection methods. 11,12 Accurately detecting the production of endogenous HNO could greatly promote the research of HNO-associated diseases. Hence, developing novel techniques to effectively measure HNO in vivo is of great significance.…”
mentioning
confidence: 99%